Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

5) f(n) = 3n-1,g(n) = 2n + 4Find (fog)(-2)

Sagot :

f(n) = 3n-1

g(n) = 2n + 4

(fog)(-2), multiply each function, and replace n by -2.

(fog)(-2) = ( 3(-2)-1 ) x (2(-2) + 4)

(fog)(-2)= (-6-1) x (-4+4)

(fog)(-2) = -7 x 0

(fog)(-2)= 0

We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.